Minimally invasive surgical techniques in vestibular function preservation in patients with cochlear implants - Wang, Ruijie; Luo, Jianfen; Chao, Xiuhua; Wang, Haibo; Fan, Zhaomin; Xu, Lei (Frontiers in Neuroscience, 2022)
Aims To investigate changes of vestibular function systematically in recipients at short and long follow-ups after a minimally invasive CI surgery. Methods In this retrospective study, 72 patients (72 ears) with minimally invasive CI were recruited. All participants selected had bilateral SNHL and preoperative residual hearing (RH) and underwent unilateral CI. They were treated to comprehensive care. All patients underwent vestibular function tests 5 days prior to CI. During the postoperative period, follow-up tests were performed at 1, 3, 6, 9, and 12 months. The contemporaneous results of caloric, cervical vestibular-evoked myogenic potential (cVEMP), ocular vestibular-evoked myogenic potential (oVEMP), and video head impulse (vHIT) tests were followed together longitudinally. Results On the implanted side, the percent fail rate of caloric test was significantly higher than that of vHIT at 1, 3, and 9 months postoperatively (p<0.05); the percent fail rate of oVEMP was higher than vHIT of SSC, PSC or HSC at 1, 3, and 9 months (p<0.05); at 3 and 9 months, the percent fail rate of cVEMP was higher than that of SSC and PSC (p<0.05). There were no significant differences in the percent fail rates among all tests at 6 and 12 months post-CI (p>0.05). The percent fail rates showed decreased trends in caloric (p=0.319) and HSC tested by vHIT (p=0.328) from 1–3 to 6–12 months postoperatively. There was no significant difference in cVEMP between 1–3 and 6–12 months (p=0.597). No significant differences on percent fail rates of cVEMP and oVEMP between short- and long-terms post CI were found in the same subjects (p>0.05). Before surgery, the abnormal cVEMP and oVEMP response rates were both lower in patients with enlarged vestibular aqueduct (EVA) than patients with a normal cochlea (p=0.001, 0.018, respectively). Conclusion The short- and long-term impacts on the vestibular function from minimally invasive CI surgery was explored. Most of the vestibular functions can be preserved with no damage discrepancy among the otolith and three semicircular canal functions at 12 months post CI. Interestingly, a similar pattern of changes in vestibular function was found during the early and the later stages of recovery after surgery.